KOMBINASI VIRGIN COCONUT OIL (VCO) DAN EKSTRAK ETANOL KELOPAK JANTUNG PISANG KEPOK (Musa paradisiaca L.) PADA FORMULASI SEDIAAN POMADE - Siti Fatimah Hanum; Pebry Nursanti Sihombing; Evi Ekayanti Ginting; Fahma Shufyani; Jefri Naldi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Pomade is an oily or waxy substance used for hairstyles. The pomade looks shiny, smooth and not dry. The properties of pomade make hairstyles look neater, while long-lasting moisturizing properties are popular with textured individuals. Method; This research was carried out experimentally, including the manufacture of ethanol extract of the banana flower petals of Kepok (Musa paradisiaca L.) using the maceration method of a combination of VCO (Virgin Coconut Oil) oil with the fishing method as a pomade preparation, with a concentration of 2%, 4%, 6%. Physical quality examination, namely organoleptic test, pH, homogeneity, stability, spreadability, irritation based on SNI 16-4955-1998, and effectiveness test using volunteers. Results; In this study, it was found that preparations that showed or showed good orgnoleptic at a concentration of 2%, 4%, 6%, fulfilled the homogeneity requirements at a concentration of 2%, 4%, 6%, good dispersion at a concentration of 4%, the irritation test did not irritate. skin, pH test has a pH value according to the pH value of pomade, good stability aimed at a concentration of 2% for 14 days. The results of the effectiveness test of pomade preparations concentrations of 2%, 4%, 6% obtained effective results at 5 hours of use compared to those on days 1, 2, 3.Use 5 hours with the category of tidy 100%, durable 66.67%, no durable 33.33%, and easy 100% of 9 volunteers. Conclusion; From this research, the ethanol extract of Kepok banana flower petals with a combination of VCO (Virgin Coconut Oil) can be formulated into pomade preparations and the stable formula is one that contains ethanol extract of Kepok banana flower petals with a 2% concentration of VCO (Virgin Coconut Oil).